The correlation of student’s motivation and self-concept: A case study in science learning - Kurniawan, Luthfiyah Azzahra; Rahmat, Adi; Winarno, Nanang; Prima, Eka Cahya (Education and Development Research, 2025)
Although the relationship between student motivation, self-perception, and achievement in science education is well established, there is still a lack of focused studies on these aspects at the lower secondary level, particularly in private school settings where student demographics and learning environments may pose unique challenges. The purpose of this study is to: (1) assess lower secondary students' motivation and self-concept in scientific learning; and (2), using correlational analysis and qualitative feedback, determine ways to improve these aspects. Using a quantitative descriptive survey design, this study assessed 60 grade 7-9 students from a private lower secondary school. The Students’ Motivation Toward Science Learning (SMTSL) and adapted Chemistry Self-Concept Inventory (CSCI) measured motivation and self-concept, respectively. Data analysis included mean scores for both variables and Spearman’s rank correlation (accounting for Liker-scale ordinality and non-normal distributions). A moderate-high level of motivation (Active learning strategies [ALS]=4.0-4.1 highest, Performance Goal [PG]=2.8-3.1 lowest) and self-concept (Positive Perception of Science Self Concept [PSSC]=3.8-3.9 highest, Mathematic Self-Concept [MSC]=2.9-3.2 lowest) with moderate positive correlation (r = 0.572, p < 0.001) underscores that self-concept and motivation are interrelated, suggests interventions should simultaneously promote active learning (to enhance ALS) while addressing mathematical confidence (to improve MSC). These findings suggest that teachers can boost engagement through active learning and confidence-building strategies, while school and policymakers should design targete interventions to support students with low scientific confidence and high performance pressure.